Revolusi Digital dalam Peradilan Agama: Membuka Jalan bagi Keadilan yang Lebih Inklusif di Indonesia - Amrar Mahfuzh Faza; Mukhlis Lubis (UNES Law Review, 2023)
This research explores the transformation in Indonesia's religious courts triggered by the current development of digital technology. A particular focus is given to how digitization affects efficiency and access to justice, particularly in remote areas. Despite improvements in the application of technology, there remains a knowledge gap regarding the social impact and inclusiveness of digitization in religious justice practice. The methodology used was qualitative with an analytical descriptive approach focusing on the study of relevant literature to gain a comprehensive understanding. The results showed that digitization has improved the efficiency of the judicial process and facilitated effective and efficient access to legal information, however there are significant infrastructure and digital literacy challenges. The findings highlight that while digitization provides benefits in accelerating case handling, gaps in digital access and literacy are major barriers to its implementation. The implication is that there is a need for improved digital infrastructure and literacy, as well as training for stakeholders to effectively integrate digital technology in the religious justice system in Indonesia.